Digital video broadcasting - terrestrial : design, streaming and application - Lee, Edmund Wee Kuan. (2013)
Digital Video Broadcasting (DVB) is a set of globally accepted open standards for digital television. It is currently being adopted by many countries over the world as the standard for broadcasting of digital television. Compared with the traditional analog broadcasting, it can offer a far more superior image and sound quality to the consumers. The analog broadcasting is gradually being replaced by the new digital broadcasting as the way of television broadcasting. Currently, there is an ongoing process termed “Digital Television Transition” that aims to completely replace the analog broadcasting in different countries with digital broadcasting within a certain timeline.